2010
DOI: 10.2478/s11756-009-0217-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, physiological, molecular and phylogenetic characterization of new environmental isolates of Acanthamoeba spp. from the region of Bratislava, Slovakia

Abstract: Protozoa of the genus Acanthamoeba are organisms that can be generally found in the environment. The focus of this study is the detection of the presence of Acanthamoeba in different water sources and samples taken from airconditioning units. The identification of Acanthamoeba isolates was based on the morphology of cysts and trophozoites as well as PCR amplification with a genus specific primer pair JDP1 and JDP2. Growth characteristics and temperature tolerance were monitored. The pathogenic potential was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
1
19
0
1
Order By: Relevance
“…Performed alignment showed 1 indel and 7 transversions among our T4 sequences ( Table VI) and revealed that one of our Acanthamoeba sp. T4 sequence (HQ632779) is identical to our three sequences obtained earlier from Polish fountain (JQ408990) and lake (JQ408989 and HQ632778) water and eight sequences from GenBank: Acanthamoeba T4 GQ342606 sequence obtained from bronchoaspirate fluid (BAL) of 15-year boy after the allogenic transplantation of bone marrow in Poland (Lanocha et al 2009), Acanthamoeba T4 GQ397463, GQ397464, GQ397467 and GQ397471 sequences obtained from Slovenian swimming pool water, swimming pool scrape and salt cave salt water (Nagyová et al 2010), Acanthamoeba sp. EF140627 sequence obtained from infected cornea of amoebic keratitis patients in Korea, Acanthamoeba polyphaga AY237735 sequence obtained from hospital water network in France and Korean Acanthamoeba lugdunensis AF005995 sequence.…”
Section: Genotypingsupporting
confidence: 78%
See 3 more Smart Citations
“…Performed alignment showed 1 indel and 7 transversions among our T4 sequences ( Table VI) and revealed that one of our Acanthamoeba sp. T4 sequence (HQ632779) is identical to our three sequences obtained earlier from Polish fountain (JQ408990) and lake (JQ408989 and HQ632778) water and eight sequences from GenBank: Acanthamoeba T4 GQ342606 sequence obtained from bronchoaspirate fluid (BAL) of 15-year boy after the allogenic transplantation of bone marrow in Poland (Lanocha et al 2009), Acanthamoeba T4 GQ397463, GQ397464, GQ397467 and GQ397471 sequences obtained from Slovenian swimming pool water, swimming pool scrape and salt cave salt water (Nagyová et al 2010), Acanthamoeba sp. EF140627 sequence obtained from infected cornea of amoebic keratitis patients in Korea, Acanthamoeba polyphaga AY237735 sequence obtained from hospital water network in France and Korean Acanthamoeba lugdunensis AF005995 sequence.…”
Section: Genotypingsupporting
confidence: 78%
“…They are isolated from water, soil, dust and air samples throughout the world. These of them, which may live also within other organisms as parasites are called amphizoic (Nagyová et al 2010) and they include Acanthamoeba spp., Balamuthia mardrillaris, Naegleria fowlerii, Sappinia pedata and probably Hartmannella vermiformis (Kuiper et al 2006;da Rocha-Azevedo et al 2009;Gianinazzi et al 2010). The source of infection is mainly water or soil containing amoebae that enter host's organism through corneal surface, nasal mucosa, and breaks in the skin or via an oral route (Schuster and Visvesvara 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Základná katalogizácia značkovaných tehál vykazuje len novoveké nápisy a vročenia (Nagy-Nagyová 2015). Pozoruhodný je nález keramických slnečných hodín z kartuziánskeho kláštora na Kláštorisku (rozmery 22,7 × 18,7 cm, hrúbka 3,8 cm -obr.…”
Section: Keramikaunclassified